2020
DOI: 10.31235/osf.io/u5wba
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rise of the War Machines: Charting the Evolution of Military Technologies from the Neolithic to the Industrial Revolution

Abstract: The causes and consequences of technological evolution in world history have been much debated. Of particular importance in many of the theoretical and empirical studies on this topic is innovation in military technologies, details of which are comparatively well preserved in the archaeology and historical record and which are often seen as drivers of broad socio-cultural processes. Here we analyze data on the evolution of key military technologies in a stratified sample of the world’s political systems from t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, a separate analysis of the evolutionary causes responsible for the increase in our measure of warfare intensity (72) finds that none of the dimensions of social complexity are included in the best models with MilTech as the response variable. In fact, that analysis finds that MilTech not affected by any polity characteristics such as territory or population size, governance or administrative complexity, monetary sophistication, and others; instead, its evolution is governed by major technological revolutions (in particular, mounted warfare and iron metallurgy), overall world population, centrality of location with respect to the major communication routes within Afroeurasia, and, weakly, by agricultural productivity (72). MilTech, thus, acts as an exogenous variable with respect to social complexity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a separate analysis of the evolutionary causes responsible for the increase in our measure of warfare intensity (72) finds that none of the dimensions of social complexity are included in the best models with MilTech as the response variable. In fact, that analysis finds that MilTech not affected by any polity characteristics such as territory or population size, governance or administrative complexity, monetary sophistication, and others; instead, its evolution is governed by major technological revolutions (in particular, mounted warfare and iron metallurgy), overall world population, centrality of location with respect to the major communication routes within Afroeurasia, and, weakly, by agricultural productivity (72). MilTech, thus, acts as an exogenous variable with respect to social complexity.…”
Section: Resultsmentioning
confidence: 99%
“…External conflict theories propose that competition between societies, usually taking the form of warfare, imposes a selection regime that weeds out relatively dysfunctional, poorly organized, and internally uncooperative polities, favoring those with larger populations and effective, centralized, and internally-specialized institutions (7,(67)(68)(69)(70)(71). The main proxy for the warfare hypothesis is the Seshat measure of the realized sophistication and variety of military technologies used by polities, MilTech (72). A large variety of sophisticated means of attack and defense serves as a quantitative proxy for the intensity of warfare in the environment of the polity, because people tend to invest in expensive armor and defenses when their societies are threatened by their neighbors.…”
Section: Data Variables For Testing Theories Main Response Variablesmentioning
confidence: 99%
“…Given that our research has provided strong empirical support for the idea that cascades of technological advances, especially in the military sphere, are an important driver of cultural macroevolution in the long run, it is legitimate to ask, what drives the evolution of technological cascades? A recent study by the Seshat project found that world population size, connectivity between geographical areas of innovation and adoption, and critical enabling technological advances, such as iron metallurgy and horse riding are strong predictors of change in military technology, whereas state-level factors such as polity population, territorial size, or governance sophistication play no major role (Turchin et al, 2021b). What is interesting about this result is that it again confirms the key role of intersocietal interactions: competition and exchange.…”
Section: Mode: Qualitative Patterns and Mechanisms Of Changementioning
confidence: 99%